2008
DOI: 10.1002/hbm.20662
|View full text |Cite
|
Sign up to set email alerts
|

Altered sleep brain functional connectivity in acutely depressed patients

Abstract: Recent evidence suggests that problems in information processing within neural networks may underlie depressive disease. In this study, we investigated whether sleep functional brain networks are abnormally organized during a major depressive episode (MDE). We characterized spatial patterns of functional connectivity by computing the "synchronization likelihood" (SL) of 19 sleep EEG channels in 11 acutely depressed patients [42 (20-51) years] and 14 healthy controls [32.9 (27-42) years]. To test whether disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
90
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 59 publications
16
90
1
1
Order By: Relevance
“…However, several topological properties, including network strength, global efficiency, and absolute path length, were significantly altered in the RGD and aMCI groups compared with controls. These findings were consistent with previous neuroimaging studies using graph analysis to study depression (Leistedt et al, 2009) and AD (Stam et al, 2007;He et al, 2008;Supekar et al, 2008;Lo et al, 2010). Lower network strength was related to the sparse connectivity of the brain networks, which suggests a reduced WM integrity in the RGD and aMCI patients.…”
Section: Discussionsupporting
confidence: 91%
“…However, several topological properties, including network strength, global efficiency, and absolute path length, were significantly altered in the RGD and aMCI groups compared with controls. These findings were consistent with previous neuroimaging studies using graph analysis to study depression (Leistedt et al, 2009) and AD (Stam et al, 2007;He et al, 2008;Supekar et al, 2008;Lo et al, 2010). Lower network strength was related to the sparse connectivity of the brain networks, which suggests a reduced WM integrity in the RGD and aMCI patients.…”
Section: Discussionsupporting
confidence: 91%
“…Similar conclusions have been mentioned in the study of brain functional networks. In sleep neuronal functional networks of depressed patients, Leistedt et al [63] indicated the functional reorganization of depressed patients lost "small-world network" (SWN) characteristics. Zhang et al [64] and Li et al [7] teams also indicated the MDD patients showed a shift toward randomization in MDD brain networks compared with the healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, these studies have used different approaches and methodologies to investigate differences in brain dynamics between depressed patients and healthy controls making it difficult to compare outcomes. For example, Lee et al (2011) used correlations between power series of channel pairs as a measure of connectivity; Leistedt et al (2009) used synchronization likelihood (Stam et al, 2003); whereas Fingelkurts et al (2007) used an in-house synchronization measure termed index of structural synchronization (Fingelkurts and Kahkonen, 2005). Although these and other EEG/MEG measures of connectivity (phase coherency, phase lag index, imaginary coherency, etc) have been shown to capture aspects of correlations/synchronization between two time series, they are known to perform differently.…”
Section: Synchronization Asymmetrymentioning
confidence: 99%